Computer Modelling and Simulation Techniques as a Tool For Aiding the Design of Orthopaedic Unilateral External Fixators – Focused on Innovative Solutions - Jasińska-Choromańska, D. (Engineering Transactions, 2001)
The paper presents the methods of modelling and simulation of the bone-external fixator system for fracture healing of long bones. Special emphasis was put on relations between clinical assumptions and the applied analytical and simulation apparatus. Concepts of application of heuristic techniques based on artificial neural networks for studying the process of bone union are presented. Together with the results of the simulation studies, some results of the examinations performed under clinical conditions are presented.